Weighing benefits in cocoa farming systems: An analysis of profitability in certified and non-certified cocoa farming schemes in Cameroon - Peter Ngek Shillie; Roland Azibo Balgah; Eteindem Frederick Mbufor (Journal of Agriculture and Rural Development in the Tropics and Subtropics)
The environmental and economic benefits of certified cocoa production are well documented in the current literature. Yet, adoption rates remain largely suboptimal, at least partially due to insufficiently documented empirical evidence on comparative advantage of certified cocoa schemes over conventional production systems. This study estimates profits in certified and non-certified cocoa farming systems in Meme Division in Cameroon. Mixed methods research design and the multistage sampling technique were applied to collect and analyse data, and comparatively estimate profits by applying the gross margins (GM), net farm income (NFI), net present value (NPV), benefit cost ratio (BCR) and internal rate of return (IRR) analyses on 460 individual cocoa farmers. The results showed that GM, NFI, NPV and BCR were significantly higher for certified cocoa farmers compared to non-certified cocoa farmers (p=0.000). The study concludes that certified cocoa production is more profitable than non-certified cocoa production, and therefore has a significant positive impact on the livelihoods of those involved. It is recommended that farmers in the study area be encouraged to adopt certified cocoa production, for example by facilitating access to relevant resources for certified cocoa production, such as access to credit and other policies and programmes designed to motivate participation.